Significant hindlimb static weight-bearing asymmetry persists for 40-weeks in a longitudinal study in two widely used rat models of surgically induced osteoarthritis knee pain - Kuo, A.; Raboczyj, A.; Nicholson, J. R.; Corradini, L.; Smith, M. T. (Frontiers in Pharmacology, 2025)
IntroductionUnrelenting osteoarthritis (OA) knee pain is the primary reason patients seek treatment that may ultimately result in knee replacement surgery. Although the anterior cruciate ligament transection (ACLT) and the ACLT plus medial meniscectomy (MMx) induced rat models of OA knee pain are well-characterized histologically, reports on changes in pain-like behaviors that persist longterm, are scant and so this is a knowledge gap.MethodsWe conducted a 40-week longitudinal study using these models in male Sprague-Dawley rats. Hindlimb static weight-bearing asymmetry was assessed using the incapacitance test. Von Frey filaments and an Analgesy-Meter were used to measure paw withdrawal thresholds (PWTs) and paw pressure thresholds (PPTs) respectively in the hindpaws.Results and discussionOur findings show significant, reproducible and long-lasting static weight-bearing asymmetry in the hindlimbs of both models (but not the sham-control group) for the 40-week study duration. Significant mechanical hypersensitivity developed in the ipsilateral hindpaws of the ACLT + MMx model (PWTs ≤8 g) which reversed spontaneously by ∼8–12-weeks. In the ACLT and the sham-groups, significant mechanical hypersensitivity did not develop in the ipsilateral hindpaws. In conclusion, hindlimb static weight-bearing asymmetry is a long-lasting, significant pain behavioral endpoint in these models suitable for assessing novel disease-modifying OA therapeutics and/or analgesic drug candidates aimed at alleviating unrelenting chronic OA knee pain in patients.